Interleukin 18 -607 A/C Gene Polymorphism is Associated With Susceptibility to IgA Nephropathy in a Chinese Han Population. Issue 10 (November 2017) - Yang, Bin; Feng, Weihua; Li, Yi; Shi, Yunying; Cai, Bei; Liao, Yun; Zhang, Junlong; Huang, Zhuochun; Wang, Lanlan
Abstract : The association between a single-nucleotide polymorphism (SNP; -607A/C) in the promoter region of the IL-18 gene with IL-18 promoter transcription activity and the level of IL-18 protein production has been observed repeatedly. However, the association between the IL-18-607A/C (rs1946518) promoter polymorphism and IgA nephropathy (IgAN) in a Chinese Han population is still unclear. A total of 166 patients with renal biopsy-proven IgAN and 198 healthy controls were recruited for this study. The SNP was genotyped by the polymerase chain reaction and the high-resolution melting method. Clinical characteristics and pathology grading of patients with IgAN were recorded at the time of the kidney biopsy. There was a significant difference in the distribution between the AA genotype and the AC/CC genotype [ P =0.007, OR (95% CI)=1.885 (1.183-3.003)]. However, no significant differences were observed between the rs1946518 SNP and quantitative traits (all P >0.05) or different pathology grades (Lee's grading system and tubular atrophy/interstitial fibrosis according to the Oxford classification) ( P =0.769 and P =0.7) of the patients. We first demonstrated that the AA genotype of the IL-18-607A/C was associated with an increased susceptibility to IgAN in this population.